Pengaruh Diklat Dan Motivasi Kerja Terhadap Kinerja Dosen di IAIN Madura - abduh, abdullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The purpose of this study was to measure, test and analyze the effect of training and work motivation on the performance of lecturers at IAIN Madura. The researcher used a quantitative approach with associative research type through a survey based on a questionnaire instrument to 66 samples (lecturers) and analyzed through multiple linear regression with the help of the SPSS 24 program. The results show that: first, education and training has a positive and significant effect on the performance of lecturers at IAIN Madura with a score of T_hitung= 2,666>T_table= 1,998 at sig level. 0.010T_table = 1,998 at the sig level. 0.009 F_table = 3.14 at the sig level. 0.002